COMPARISON ALGORITHM BASED ON IMAGE STRUCTURE IN PERSONAL RECOGNITION - Mahkamov Anvarjon Abdujabborovich; Jumayev Turdali Saminjonovich (American Journals Publishing, 2025)
This article presents an approach to identifying the identification features of a person's image and comparing images based on this. By changing the values of the parameters of this algorithm aimed at identifying the identification features in the image, several training samples are formed. Based on the obtained training samples and the shape of the image, a comparison is made and the algorithm is evaluated.
Keywords: Image, class, object, identification feature detection algorithm, contour line separation, training sample, training, classification, quality functional.